Population growth and economic development empirical evidence from the Philippines - Furuoka, Fumitaka (Philippine Journal of Development)
Various concerns have been expressed about the ability of the world economy to sustain the ever-expanding world population. This paper aims to provide additional empirical evidence to the ongoing debate about the impact of population growth on economic development with the Philippines as a case study. The findings of this study indicate the existence of a long-run equilibrium relationship between economic performance and population growth in the Philippines. That is, economic development in the Philippines has had a positive impact on population growth in the country. This empirical result supports the hypothesis of "economic development-induced" population growth, which is the key outcome of the study.